Longitudinal evaluation of upper motor neuron burden scales in primary lateral sclerosis. Issue 1 (2nd January 2021) - Floeter, Mary Kay; Wu, Tianxia
Abstract: Objective: To assess whether published scales for measuring upper motor neuron burden (UMNB) show longitudinal change in patients with primary lateral sclerosis (PLS). Design: Retrospective calculation of three UMNB scales on a prospectively collected dataset from 53 patients with PLS enrolled in a longitudinal natural history study with at least 2 evaluation visits. UMNB scales were calculated according to their published descriptions. Non-linear trends over time of UMNB scale scores and slopes were calculated for each patient and correlations between UMNB scores and clinical measures were assessed. Results: All three UMNB scales exhibited increasing scores over the first 7.8 years of symptoms, with a flattening in slope after approximately 8 years. A scale used in imaging studies and the UPENN UMNS scale provided a better fit to the dataset than the MGH UMNB scale. All three UMNB scales exhibited moderate correlations with some clinical measures of movement, such as finger-tapping rate and timed gait. Correlations were strongest for the UPENN UMNS, which was also moderately correlated with the revised ALS functional rating scale. Conclusion: In a cohort of PLS patients enrolled in a natural history study, the three UMNB scales exhibited modest linear increases over the first 8 years of symptoms, followed by a plateau. Future clinical trials in PLS should consider stratification of patients by disease duration. UMNB scales may be useful secondary outcomes, but more sensitive primary outcome measures are needed for clinical trials for PLS.